What happens in Amsterdam - Solomon, Rachel Lynn (Berkley Romance, 2025)
"Falling in love with your husband is anything but convenient in this steamy romance from the New York Times bestselling author of Business or Pleasure. Dani Dorfman has somehow made it to her thirties without knowing what she wants to do with her life. So when an office romance ends poorly and gets her fired, she applies for a job in Amsterdam, idly dreaming of escaping the mess she's created, but never imagining she'll actually get it. Except she does. By the end of her first week in Amsterdam, she's never felt more adrift or alone. Then she crashes her bike into her high school ex-boyfriend-and suddenly life is blooming with new opportunities. Wouter van Leeuwen was a Dutch exchange student Dani's family hosted, a forbidden love that ended in a painful breakup. Years later, there's still sizzling chemistry between them, and okay, maybe a little animosity. More importantly, Wouter needs to be married to inherit a gorgeous family home on a canal-and when Dani's job falls apart, she needs a visa. As the marriage of convenience pushes them together in unexpected ways, Dani must decide whether her new life is yet another mistake-or if it's worth taking a risk on a second chance"--